2008
DOI: 10.1111/j.1525-1438.2007.01131.x
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Pap screening and human papillomavirus among women attending clinics in Medellín, Colombia

Abstract: This study evaluated Pap screening and human papillomavirus (HPV) knowledge in a population of Colombian women as a possible contributing factor of low cervical cancer screening success. This is a descriptive, cross-sectional analysis of 454 women who were approached in five different hospitals and clinics throughout Medellín, Colombia. Of them, 449 females agreed to participate and answered a standardized face-to-face questionnaire regarding Pap screening and HPV knowledge. Using logistic regression, predicto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
38
4
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 22 publications
11
38
4
6
Order By: Relevance
“…Furthermore, only 15 % from the participants stated that HPV causes cervical cancer and 7 % knew that HPV was a virus or a sexually transmitted disease which can be transmitted during sexual intercourse with a man. The finding of this study also not incongruent with a study done by Hanisch et al (2007) who demonstrated that majority of the respondents (79.3%) were categorized into low knowledge on HPV. Only 7.8% of the respondents possessed high knowledge on HPV and 12.9% possessed medium knowledge on HPV.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Furthermore, only 15 % from the participants stated that HPV causes cervical cancer and 7 % knew that HPV was a virus or a sexually transmitted disease which can be transmitted during sexual intercourse with a man. The finding of this study also not incongruent with a study done by Hanisch et al (2007) who demonstrated that majority of the respondents (79.3%) were categorized into low knowledge on HPV. Only 7.8% of the respondents possessed high knowledge on HPV and 12.9% possessed medium knowledge on HPV.…”
Section: Discussioncontrasting
confidence: 55%
“…Other study supported the lower education background reflect the lower knowledge on HPV. The result showed those who had elementary school education or less were 3.18 times higher for having lower knowledge on HPV (95% CI 1.82-5.57) (Hanisch et al, 2007).…”
Section: Discussionmentioning
confidence: 84%
“…Middle or high socioeconomic class Colombian women are more likely to have a high knowledge of HPV than were those of low socioeconomic class (p = 0.002) [32]. The effect of high school or higher education on HPV knowledge is significant (p = 0.006) [32].…”
Section: Colombian Attitudes Towards Hpv Hpv-related Diseases and Hmentioning
confidence: 85%
“…Knowledge of CC screening via Pap testing (97.6% of sampled women) did not translate into HPV knowledge [32]. In Arauca, Bogotá, Cartagena, and Manizales parents of daughters younger than 12 years old were resistant to HPV vaccination to prevent STI, and were concerned of sexual disinhibition, but would accept HPV vaccination to prevent CC [38].…”
Section: Colombian Attitudes Towards Hpv Hpv-related Diseases and Hmentioning
confidence: 99%
“…En un estudio llevado a cabo en Medellín, se demostró que las mujeres tienen un buen conocimiento acerca de los beneficios del uso de la misma (27). Estas dos observaciones concuerdan con lo observado en México, en el que se demostró que el factor principal para la utilización del programa de detección temprana de cáncer es el conocimiento de la utilidad de la citología (28) e, indirectamente, sugieren que aspectos tales como las deficiencias en la calidad de la citología o las barreras en el acceso a los servicios de colposcopia y tratamiento pudieran explicar el hecho de que las tasas de mortalidad de cáncer de cuello uterino en Colombia permanezcan altas.…”
Section: Discussionunclassified